Development of a Sustained Release, Liquid Oral in situ Gelling System of Montelukast Sodium with Improved Bioavailability: Equivalence Testing using Earth Mover’s Distance - Mathews, Mrs. Rashmi (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The present study aims at the development of a sustained release liquid oral in situ gel of the antiasthmatic drug montelukast sodium with improved bioavailability and patient compliance. The drug has a short biological half-life of 2.5–5.5 h, an oral bioavailability of 64% and is commercially available only as solid dosage forms. Materials and Methods: The formulations were statistically designed using central composite design, suitable proportions of thermosensitive polymers such as Pluronic F127, Xyloglucan and other excipients added and a simple mixing (cold method) used for the preparation. The effect of the factors on various responses was evaluated and optimization was done. Results: The optimized formulation showed a mean viscosity of 0.039 Pas, gelled at body temperature, gave 94.18 ± 2.15 % drug release in 12 h. In vivo studies on New Zealand male rabbits revealed a Cmax of 192.91 ± 13.363 ng/ml in 1 h and 12 h sustained release. The AUC0–α (4767.942 ± 412.915 ng h/ml) showed 3.8-fold increase in bioavailability. Stability studies indicated a 2-year shelf life at 4°C. ϴtest (0.78690) < ϴstd (0.7963) obtained using Earth mover’s distance revealed that the pharmacokinetic profile of the optimized formulation was better than the reference drug solution. Conclusion: This elegant, less bulky, liquid oral in situ gelling system with pH-independent release would also be patient compliant and could pave way for a better approach to drug delivery.